Comprehensive rehabilitation programme after resection of a humerus osteosarcoma and postresectional Mutars endoptothesis - Antas, Paulina; Szczypiór-Piasecka, Karina; Mińko, Alicja; Antczak, Krzysztof (Journal of Education, Health and Sport, 2021)
Introduction: Bone sarcomas are malignant neoplasms of mesenchymal origin, the occurrence of which is rare. The most commonly diagnosed primary bone cancer is spindle cell osteosarcoma. Bone sarcomas are mainly located in the long bones of the limbs, most often in the femur, tibia and humerus. The aim of this study is to present a program of comprehensive rehabilitation after resection of humerus osteosarcoma and post-resection Mutars arthroplasty. Materials and methods: The work was written on the basis of the medical history of a patient treated at the Department of Orthopedics, Traumatology and Oncology of the Movement Organ of the Pomeranian Medical University in Szczecin. Results: Hospital rehabilitation usually takes about 7 days. Its main goal is to return the patient to optimal functioning and daily activities as quickly as possible. Post-hospital rehabilitation takes much longer than hospital rehabilitation and depends on the patient's condition. Its main goal is to regain muscle strength by the patient. Conclusion: Rehabilitation is an important element of the treatment of cancer patients. Early initiation of rehabilitation brings tangible benefits during treatment and the patient's recovery.